2010
DOI: 10.2310/6670.2009.00041
|View full text |Cite
|
Sign up to set email alerts
|

Angiolymphoid Hyperplasia with Eosinophilia Presenting as a Giant Axillary Artery Aneurysm

Abstract: Angiolymphoid hyperplasia with eosinophilia (ALHE) is an unusual vascular tumor most frequently located in the superficial head and neck. Noncutaneous localization of this pathology in large arteries presenting as a pulsatile mass is extremely rare. We describe an adult male with a giant left axillary artery tumor secondary to ALHE. ALHE should be considered in the differential diagnosis of localized peripheral arterial masses, especially in young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Our review of the literature revealed 24 well documented cases [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] . We did not include cases with poor documentation [27] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review of the literature revealed 24 well documented cases [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] . We did not include cases with poor documentation [27] .…”
Section: Discussionmentioning
confidence: 99%
“…The ALHE lesion in our patient involved the common digital artery and there were two other previously reported cases with common digital artery involvement [1] , [23] . Involvement of the radial artery [10] , [20] , ulnar artery [8] , [9] , [14] , brachial artery [2] , [11] , and axillary artery [12] , [13] have also been reported. Total excision of the involved artery is curative; and reconstruction with vein grafts is only mandatory after axillary and brachial artery excisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] The noncutaneous localization of this pathology in the large arteries presenting as a pulsatile mass is extremely rare. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…About 22 cases have been reported, involving in order of decreasing frequency: temporal artery [14–20], radial artery [2124], brachial artery [11, 12], ulnar artery [25, 26], axillary artery [27, 28], subclavian artery [29], facial artery [30], post-auricular artery [31], popliteal artery [32], common carotid artery [33] and occipital artery [12]. The lesion can grow entirely in the lumen of the blood vessel developing occlusive symptoms (such as weakening of the pulse in peripheral arteries) or it can originate from the vascular wall and developing outside with compression of adjacent structures.…”
Section: Discussionmentioning
confidence: 99%